Can One Donation a Day Keep Depression Away? Three Randomized Controlled Trials of an Online Micro-Charitable Giving Intervention - Zhang, Yuyang; Jiang, Qianyu; Luo, Yushen; Liu, Jinting (Psychological Science, 2025)
Prosocial interventions grounded in social interactions have shown limited effectiveness in alleviating depressive symptoms, possibly because of the discomfort and unease that depressed individuals experience during such interactions. We developed and examined an innovative prosocial intervention—an online micro-charitable giving intervention, in which individuals voluntarily donated at least one Chinese cent (¥0.01, or about $0.0014) daily. We conducted three preregistered, 2-month randomized controlled trials with depressed individuals (Sample 1: N = 125, Sample 2: N = 296, Sample 3: N = 462). Results showed that, compared with the waitlist group, the intervention group exhibited significantly greater improvements in both depressive symptoms (Cohen’s d s = −0.19 to −0.46) and emotional positivity (Cohen’s d s = 0.22 to 0.49), and that emotional positivity mediated the intervention’s effect on the reduction of depressive symptoms. Exploratory analysis found a slightly larger intervention effect for generous donors than for minimal donors. This low-cost, easily accessible prosocial intervention holds potential for the prevention of depression. Statement of Relevance Can donating one cent (specifically one Chinese cent, or about $0.0014) alleviate depressive symptoms? We have developed a practical and effective intervention—donating at least one cent daily on an online charity platform—and have discovered that this intervention effectively mitigates depressive symptoms in depressed individuals. Despite the nominal purchasing power of one cent in contemporary society, this act of giving has been shown to significantly enhance mental health. Our findings could be relevant to everyone in society; charitable donations promote societal harmony and, in addition, offer a cost-effective way to alleviate depressive symptoms. As the intervention instruction asserts, “Charity encompasses love, regardless of its size, as even one cent holds value.”